SLAUGHTER WEIGHT AND FAT BROILER CHICKEN FED FERMENTED RATIONS WITH LIGNOCELLULOLYTICS PROBIOTIC BACTERIA - N. K. A. A., Suarningsih; Mudita, I M.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2022)
This research aims to determine the effects of fermented rations with lignocellulolytics probiotic bacteria on slaughter weight, percentage of abdominal fat and subcutaneous fat of broiler chickens. The research was conducted at Sesetan Farm, Faculty of Animal Husbandry, Udayana University in May to June 2020. The design used Completely Randomized Design (CRD) with 5 treatments and 4 replications. Each experimental unit was filled with 3 chickens. The five treatments are chickens given commercial rations (RK), fermented rations without lignocellulolytics probiotic bacteria (RF0), fermented ration with 5% Bacillus subtilis BR 4 LG bacteria (RF1), fermented ration with 5% Bacillus sp . BT 3 CL bacteria (RF2), and fermented ration with 5% Bacillus sp . BT 8 XY bacteria (RF3). The observed variables were slaughter weight, percentage of pads fat, mesentery fat, ventricular fat and subcutaneous fat. The results showed that the treatment of RF1, RF2 and RF3 resulted in slaughter weight and the subcutaneous fat percentage which was significantly (P<0.05) higher than RF0, but in general it had no significant effect (P>0.05) on percentage of abdominal except the pads fat. The RF1, RF2 and RF3 treatments resulted was significantly (P<0.05) lower slaughter weight, abdominal fat and subcutaneous fat percentages compared to the RK treatment. Based on the results of the study, concluded that the fermented ration of lignocellulolytics probiotic bacteria as much as 5% got the slaughter weight, the percentage of abdominal fat and subcutaneous fat was lower than the commercial ration treatment, but higher than the fermented ration without lignocellulolytics probiotic bacteria.   Keywords: Broiler, Abdominal Fat, Subcutaneous, Lignocellulolytics